Analisis Kebijakan Peraturan Bupati Jember Nomor 2 Tahun 2014 tentang Pencegahan dan Penanggulangan HIV/AIDS di Kabupaten Jember - Husni Abdul Gani (Fakultas Kedokteran Gigi Universitas Jember, 2015)
54 The report of people living with HIV/AIDS (PLWHA) in Jember district since 2004 until 2014 always increase every year. According to reports from Jember District Health Office ( 2015 ), until August 2015, cases of PLHA has reached 2,048 . It represents the third highest case in East Java after Surabaya and Malang . Referring to the high incidence of HIV/AIDS in Jember , the prevention and control of HIV/AIDS should have a strong legal policy. Thus the policy of the Regent of Jember Number 2 in 2014 on the Prevention and Control of HIV / AIDS in Jember was very strategic in engaging all elements in the government (SKPD) related as well as on the participation of the entire community as well as at the level of district, and rural and urban districts. This study aimed to analyze the policy of the Regent of Jember Number 2 in 2014 on the Prevention and Control of HI V/AIDS in Jember . This research is descriptive analytic with logical thinking approach to policy analysis , using the theory of Triangle Policy Analysis by Buse et al (2005 ) which includes : conteks , content , process and actors . Research was conducted on January until March 2016. The data obtained will be analyzed and linked to theories and concepts within the scope of health policy. The results showed that in terms of conteks included in situational factors or 'focusing event' is the discovery of HIV / AIDS cases in Jember very high that it becomes one of 78 District/City which received special attention from the NAC. While structural factors, namely the issuance of the East Java Provincial Regulation Number 5 in 2004 on the Prevention and Control of HIV/AIDS in East Java and Jember Regent Regulation which Number 45 on the Main Tasks and Functions Organization Jember district health office. In terms of content mentions that the contents of the policy consists of Chapter I. General Provisions, Chapter 2. Goals, Chapter III. Prevention and Control, Chapter IV. Rights of PLHA, Chapter V. Prohibition, Chapter VI. Institutional and Chapter VII. Closing. In terms of process, the enactment of the East Java Provincial Number 5 in 2004 on the Prevention and Control of HIV / AIDS in East Java, and the The policy of the regent of Jember which number 45 on the Main Tasks and Functions Organization of the Health Department of Jember. The policy of the prevention of HIV/AIDS was not separated from only the advocacy of Department of Health and KPAD of Jember Regency against the local authorities as well as support from the relevant agencies. From the actor, in the personal of the HIV and AIDS PreventionTeam was from the district, sub-district, and villages. That policy of Jember Regent in the regulation which Number 2 in 2014 on the Prevention and Control of HIV / AIDS in Jember Regency was very effective in providing a strong legal policy on a program of prevention and control of HIV and AIDS in Jember.